Fractionation of Citronella Oil and Identification of Compounds by Gas Chromatography-Mass Spectrometry - Anwar, Yelfi; Siringoringo, Victor S (Pharmaceutical Sciences and Research, 2020)
Citronella oil is one of the most important essential oils and is widely used in the pharmaceutical, cosmetic and food industries. However, the selling price of citronella oil is still low, so efforts are needed to increase its added value by isolating the active components such as citronellal, citronellol and geraniol. This study aims to isolate the active ingredients of citronella oil that have higher economic added value. Citronella oil was obtained by the process of distillation of Cymbopogon nardus (L.) Rendle leaves. The essential oil was then fractionated by a vacuum fractionation process. The essential oil fraction was identified by Gas Chromatography - Mass Spectrometry (GC-MS). Fractions obtained from the fractionation process were identified, and the results were: F1 (D-Limonene: 72.89%), F2 (Citronellal: 50.13%), F3 (Citronellal: 74.89%), F4 (Citronellal: 88.56%), F5 (Citronellal: 84.89%), F6 (Citronellal: 55.38%), F7 (Citronellol: 57.42%), F8 (Citronellol: 44.73%), F9-1 (Geraniol: 65.56%), F9-2 (Geraniol: 64.41%) and residual (Geraniol: 32.04%). Based on these results, several active compounds from citronella oil can be obtained using the vacuum distillation fractionation method.